Level of Awareness of Boat Captains in Terms of International Regulations for Preventing Collision at Sea in Region V1 (London Journal of Research In Science: Natural and Formal, 2024)
The safety of life at sea is a very important aspect in terms of navigation. The purpose of the study is to determine the level of awareness of the Boat Captains in terms of sounds and light signals and lights and shapes on Collision Regulations by using the validated questionnaires that the author was provided based on the International Collision Regulations for Preventing Collision at Sea. The study was conducted in the different areas of Region V1 namely: Boracay Island Malay, Aklan, Estancia, Roxas City Capiz, and Guimaras Province. The study was conducted last November 2018 to November 2019. Participants of the Modified Basic Safety Training Course with Typhoon Awareness and Collision Regulations conducted by the Maritime Industry Authority, Region VI Iloilo City, and Iloilo State College of Fisheries, were utilized as respondents of the study. The respondents were composed of One Hundred Eighty boat captains through stratified sampling using Slovin’s formula. A qualitative/Quantitative research design was employed in the study. Open-ended validated questionnaires were administered to the selected respondents. Focus group discussion was conducted to get reliable data from their personal experiences at sea. Answered questionnaires were gathered, tabulated, and analyzed using appropriate statistical tools. The results of the study in the sounds and lights signal the mean of the pretest is 3.05 knowledgeable and the level of awareness in terms of lights and shapes the mean of pretest is 5.86  it is knowledgeable.  The Collision Regulations training for the boat captains must be continued to improve their level of awareness and they need it in their profession. The MARINA must provide a Memorandum Circular about the Boat Captains that they must have a Certificate on the “International Collision Regulations Course” so that they are aware of the Rules of the Road and they can apply their profession and minimize or prevent whatever accidents happen onboard.
Keywords: Forensic Anthropology Cases. Forensic Anthropology Laboratory Identification. Uruguay